2019
DOI: 10.1111/wrr.12739
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility of different burn wound dressings

Abstract: A variety of wound dressing are available for burns. Furthermore, although their impacts on wound healing have been studied sufficiently, their effects on blood remain unclear. Meanwhile, this aspect is extremely important, since blood interacts with the wound dressing, especially in extensive burn injuries. Therefore, the aim of this study is to evaluate the hemocompatibility and immunogenicity of different burn wound dressings. Accordingly, human whole blood (n = 5) was anticoagulated with heparin, treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…As reported in our previous study, 3 only the plasma gained from the incubation of blood with sample D ( EZ Derm ) showed a significantly increased SC5b‐9 concentration (1428 ± 278.7 ng/mL) indicating a significant activation of the whole complement system. However, the plasma processed from incubation of blood with sample G ( Burntec ) nonetheless revealed a noticeable higher SC5b9 concentration (1283 ± 387.9 ng/mL).…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…As reported in our previous study, 3 only the plasma gained from the incubation of blood with sample D ( EZ Derm ) showed a significantly increased SC5b‐9 concentration (1428 ± 278.7 ng/mL) indicating a significant activation of the whole complement system. However, the plasma processed from incubation of blood with sample G ( Burntec ) nonetheless revealed a noticeable higher SC5b9 concentration (1283 ± 387.9 ng/mL).…”
Section: Resultssupporting
confidence: 75%
“…The complement system consists of a tightly regulated network of proteins and its activation results in the formation of membrane attack complex C5b‐9. Recently, we reported that some wound dressings caused complement activation at the interface of wound dressing and whole blood 3 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations